2017
DOI: 10.1016/j.acha.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Disjoint sparsity for signal separation and applications to hybrid inverse problems in medical imaging

Abstract: Abstract. The main focus of this work is the reconstruction of the signals f and g i , i = 1, . . . , N , from the knowledge of their sums h i = f + g i , under the assumption that f and the g i 's can be sparsely represented with respect to two different dictionaries A f and Ag. This generalizes the well-known "morphological component analysis" to a multi-measurement setting. The main result of the paper states that f and the g i 's can be uniquely and stably reconstructed by finding sparse representations of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…However, in [1], the authors were able to recover µ (independently of the light transfer model used) from a single measurement of E (again using a sparsity method, assuming different degrees of smoothness of the coefficients and the fluence). In [6,7] it was shown that this problem is uniquely solvable if two measurements of E (corresponding to well-chosen boundary illuminations g 1 , g 2 ) are available.…”
mentioning
confidence: 99%
“…However, in [1], the authors were able to recover µ (independently of the light transfer model used) from a single measurement of E (again using a sparsity method, assuming different degrees of smoothness of the coefficients and the fluence). In [6,7] it was shown that this problem is uniquely solvable if two measurements of E (corresponding to well-chosen boundary illuminations g 1 , g 2 ) are available.…”
mentioning
confidence: 99%
“…10,11 However, PA images are not directly representative of the underlying tissue structure because spatial variations in the illumination pattern cause the optical energy to be absorbed non-uniformly throughout the tissue. If φ(r) is the optical fluence generated by the laser within the tissue, then we have…”
Section: Quantitative Photoacoustic Imagingmentioning
confidence: 99%
“…Numerically speaking, multiplying a vector by the Jacobian J h κ,μ or its transpose is relatively cheap: one only needs to perform elementwise multiplications of vectors and matrix-vector multiplications with sparse matrices, and to operate with the inverse of the FEM system matrix K on a vector. However, when the number of degrees of freedom and/or illuminations is very high, the sizes of the matrices G (1) and G (2) may become impractically large. In this case, one can continue the analysis to avoid forming the matrices G (1) and G (2) altogether, but the details are omitted here for brevity.…”
Section: ∂ωmentioning
confidence: 99%
“…However, when the number of degrees of freedom and/or illuminations is very high, the sizes of the matrices G (1) and G (2) may become impractically large. In this case, one can continue the analysis to avoid forming the matrices G (1) and G (2) altogether, but the details are omitted here for brevity.…”
Section: ∂ωmentioning
confidence: 99%